The Abundance Analysis of Mangrove Crab (Scylla spp.) in the Mangrove Area at Senik Hamlet, Bedono Village, Sayung Subdistrict, Demak District - Miftahul Adha; Siti Mukhlisoh; Dian Triastari Armanda (Journal of Natural Sciences and Mathematics Research, 2016)
The abration at Senik hamlet, Bedono village, Demak district has alternated the land became mangrove ecosystem’s area. This ecosystem supply the habitat such as group of mangrove crab (Scylla sp). The purpose of this research to analyze the abundance of mangrove crab at various location in the mangrove’s ecosystem at Senik’s hamlet. The mangrove crabs sampling are taken at three station in the Rejosari The result of variances analyzis prove there are the significant differences (Fhitung=17,67; α=0,05) in the abundance of mangrove crab among station. The most abundant of mangrove crab in the station III (815 ind/Ha), then Station II (563 ind/Ha), and Station I (341 ind/Ha), The Domination of mangrove crab in the three of station is Scylla tanquebarica species (female and the age is adolescent). The analyzis result of Pearson Products Moment at the environment parameter obtained that the water salinity (r=0,77) and the depth of water (r=0,72) to be the most powerfull positive correlation with the abundance of mangrove crab. The conclusion of this research is the height of the abundance of mangrove crab at Senik’s Hamlet supported by the combination of various environment factor, especially the salinity factor, the water depth, and the density of mangrove vegetation. ©2016 JNSMR UIN Walisongo. All rights reserved